2018
DOI: 10.1021/acs.jpclett.8b01997
|View full text |Cite
|
Sign up to set email alerts
|

Deconvolution of Tunneling Current in Large-Area Junctions Formed with Mixed Self-Assembled Monolayers

Abstract: Whereas single-component self-assembled monolayers (SAMs) have served widely as organic components in molecular and organic electronics, how the performance of the device is influenced by the heterogeneity of monolayers has been little understood. This paper describes charge transport by quantum tunneling across mixed SAMs of n-alkanethiolates of different lengths formed on ultraflat template-stripped gold substrate. Electrical characterization using liquid metal comprising eutectic gallium-indium alloy reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 38 publications
1
42
0
1
Order By: Relevance
“…Katsouras et al8g examined the tunneling behaviors of large‐area junctions formed with mixed SAMs composed of n ‐alkanethiolates or n ‐alkanedithiolates of different lengths (C n X; n = number of carbons, X = end group, either monothiol (MT) or dithiols [DT]), and demonstrated the remarkable effect of molecular dilution on the on‐surface supramolecular structure of molecules, which significantly influenced the electrical characteristics of top contact and molecules in different microenvironments. They used the junctions of the form Au/SAM//PEDOT:PSS/Au, where PEDOT:PSS is poly(3,4‐ethylene‐dioxythiophene)‐poly(styrenesulfonate) as an interfacial layer to protect delicate monolayer surfaces against the gold top‐electrode deposition.…”
Section: Mixed Molecular Electronicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Katsouras et al8g examined the tunneling behaviors of large‐area junctions formed with mixed SAMs composed of n ‐alkanethiolates or n ‐alkanedithiolates of different lengths (C n X; n = number of carbons, X = end group, either monothiol (MT) or dithiols [DT]), and demonstrated the remarkable effect of molecular dilution on the on‐surface supramolecular structure of molecules, which significantly influenced the electrical characteristics of top contact and molecules in different microenvironments. They used the junctions of the form Au/SAM//PEDOT:PSS/Au, where PEDOT:PSS is poly(3,4‐ethylene‐dioxythiophene)‐poly(styrenesulfonate) as an interfacial layer to protect delicate monolayer surfaces against the gold top‐electrode deposition.…”
Section: Mixed Molecular Electronicsmentioning
confidence: 99%
“…Although the field of molecular and organic electronics has long utilized pure molecular systems, studies on how charges traverse across multicomponent molecular systems have only recently emerged . This review article focuses on the emergence of, and recent advances in mixed molecular electronics, defined as an electronics field exploiting heterogeneous molecular systems such as mixed SAMs ( Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have attempted to alter their electrical, optical, and mechanical properties to improve device performance. In these studies, the surface characteristics of the organic layers were important parameters for energy‐level alignment in electronic devices and were influenced by the fabrication process . Molecular layer deposition (MLD) is distinct from conventional solution‐based methods, as it is a vapor‐phase technique for the fabrication of organic and organic–inorganic hybrid thin films.…”
Section: Introductionmentioning
confidence: 99%
“…While these findings still focus on signature gene markers of cell subpopulations (Aarts et al, 2001;Arienti et al, 2017;Karaayvaz et al, 2018), but in our study we mainly analyze subclonal proportion in tissue bulks. Based on the deconvolution algorithm (Jin et al, 2018;Newman et al, 2015;Zeng et al, 2019), we connected single-cell level with bulk-tissue level by estimating subclones' proportion in tumor tissue then reveal genetic features, biological functions and clinical behaviors of TNBC subclones. And in result, we found that distinct subclone has its special function such as "regulation of T cell activation" in C1, "regulation of ARF GTPase activity" in C3, "programmed cell death" in C5 and so on.…”
Section: Introductionmentioning
confidence: 99%